THE EFFECTIVENESS OF COGNITIVE BEHAVIOR THERAPY STRESS INOCULATION ON STUDENT STRESS MANAGEMENT AT SMAN 1 PANGKALAN KERINCI - Dea Aulia; Firman; A. Muri Yusuf (Yayasan Citra Dharma Cindekia, 2021)
Stress is a pressure if left unchecked will become a disease that can hinder the activities of daily life. Stress is a common thing that is often experienced by a person. But stress will also be something that is dangerous if someone can't manage it. One of the trainings provided in the CBT approach to stress management is Stress Inoculation training, for that the purpose of this study is to determine the effectiveness of cognitive behavior therapy stress inoculation on stress management.